Tillage and Crop Rotation Shape Soil-borne Oomycete Communities in Corn, Soybean and Wheat Cropping Systems - Gahagan, Alison Claire (Université d'Ottawa / University of Ottawa, 2023)
Soil-borne oomycetes include plant pathogens that cause substantial losses in the agricultural sector. To better manage this important group of pathogens, it is critical to understand how they respond to common agricultural practices, such as tillage and crop rotation. Here, a long-term field experiment with a split-plot design with tillage as the main plot factor (conventional tillage [CT] vs. no till [NT], 2 levels) and rotation as the subplot factor (monocultures of soybean, corn, or wheat, and corn-soybean-wheat rotation, 4 levels) was sampled. Post-harvest oomycete communities were characterized over three consecutive years (2016-2018) by metabarcoding the Internal Transcribed Spacer 1 (ITS1) region of soil DNA extracts. The community contained 292 Amplicon Sequence Variants (ASVs) and was dominated by Globisporangium spp. (85.1% in abundance, 203 ASV) and Pythium spp. (10.4%, 51 ASV). NT decreased diversity and community compositional structure heterogeneity, while crop rotation only affected the community structure under CT. Soil and crop health represented by soybean seedling vitality was lowest in soils under CT cultivating soybean or corn, while grain yield of the three crops responded differently to tillage and crop rotation regimes. The interaction effects of tillage and rotation on most oomycetes species accentuated the complexity of managing these pathogens.
Keywords: Agronomy; Amplicon Sequencing; Crop Rotation; Oomycetes; Tillage